Authoritarian Parenting and Emotional Maturity in Juvenile Delinquency Tendencies: Pola Asuh Otoriter dan Kematangan Emosional pada Kecenderungan Kenakalan Remaja - Deinira Putri Febrianti; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Juvenile delinquency represents a growing social concern characterized by behaviors that violate social norms, laws, and community expectations during adolescence. Specific Background: Internal factors such as emotional maturity and external factors such as parenting style are frequently associated with adolescent behavioral development, particularly within family environments that shape emotional regulation and social adjustment. Knowledge Gap: Despite increasing reports of adolescent delinquency, empirical evidence simultaneously examining authoritarian parenting and emotional maturity in relation to delinquent behavior tendencies among Indonesian high school students remains limited. Aims: This study aimed to determine the relationship between authoritarian parenting and emotional maturity with tendencies toward juvenile delinquent behavior among senior high school and vocational students in Krian District. Results: Using a quantitative correlational design with quota sampling of 337 students and multiple linear regression analysis, findings indicated that authoritarian parenting and emotional maturity jointly showed a significant relationship with juvenile delinquency tendencies, accounting for 53% of variance. Authoritarian parenting demonstrated a stronger positive relationship with delinquent behavior, whereas emotional maturity showed a significant negative relationship. Novelty: The study provides integrated empirical evidence highlighting the simultaneous contribution of parenting style and emotional developmental factors within a single regression model among adolescents in a local educational context. Implications: These findings underscore the importance of reducing authoritarian parenting practices and promoting emotional maturity development through family and school-based interventions to address adolescent delinquency tendencies and support healthier psychosocial development. Highlights: Parenting Characterized by Strict Control Is Strongly Associated With Higher Levels of Rule-Violating Conduct Among Students. Higher Emotional Regulation Capacity Corresponds With Lower Likelihood of Problematic Adolescent Actions. Combined Psychological and Family Variables Explain More Than Half of Behavioral Variation Observed in Participants. Keywords: Authoritarian Parenting, Emotional Maturity, Juvenile Delinquency, Adolescent Behavior, Parenting Style